Analisis Peran dan Pengaruh Teknologi dalam Dunia Pendidikan - Rts Rista Maharani; Yupita Dwi Saputri (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The purpose of this research is to find out the role and influence of technology in the world of education. This research method is a qualitative research using library research methodology. Technology in education is a system used to guide teaching so that the desired results can be achieved. There is always a growing gap between the progress of education and technology and the progress of mankind. In the process, educational technology requires several components, such as tools and components used to collect information, analyze it, and solve problems that may arise. The benefits include adding information, increasing learning capacity, and simplifying the learning process of this technology.